Patch containing cannabidiol

CN116327738BActive Publication Date: 2026-10-20POWIN BIOMEDICAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111579580.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-22
Publication Date
2026-10-20
Estimated Expiration
2041-12-22

AI Technical Summary

Technical Problem

[0004]从生物制药的角度来看,尽管大麻二酚在药理上具有多种有益功效,而皮肤作为其中一种药物输送途径,虽然一般都认为小分子药物能够轻易穿透皮肤最外层的角质层,但大麻二酚的化合物本身是脂溶性,具有不易溶于水(poor aqueous solubility)及渗透穿透率不佳(poor permeability)等特性,造成大麻二酚传输效率低,进而影响透皮吸收率,使得大麻二酚的生物利用度(bioavailability)变低,导致治疗效果受到限制

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116327738B_ABST
    Figure CN116327738B_ABST
Patent Text Reader

Abstract

The present application relates to a patch containing cannabidiol for transdermal delivery of cannabidiol to a subject in need thereof. The patch comprises a support and a gel layer combined on the support, wherein the gel layer comprises cannabidiol; the content of the cannabidiol is about 0.2-2% (w / w) of the total mass of the gel layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates generally to the field of pharmaceutical technology. Specifically, it relates to a pharmaceutical composition containing cannabidiol (CBD), and more particularly to a patch containing CBD. Background Technology

[0002] In recent years, nanotechnology has become one of the research focuses of various fields. Many materials exhibit completely different physical, chemical, and biological properties at the nanoscale compared to their normal state. When nanotechnology is applied to the biomedical field, especially to improve drug delivery systems, the design of molecular nanoscales can effectively improve the delivery mode of drug delivery systems, enhance their bioavailability, and improve the uniformity, dispersibility, and absorption of formulations, thereby enhancing the efficacy of drugs. For example, compounds can be encapsulated with polymers or lipids to form liposomes, solid lipid nanoparticles, or polymeric nanoparticles under appropriate preparation conditions, which have been widely used.

[0003] Cannabidiol (CBD) is an active ingredient in cannabis plants and belongs to the cannabinoid family. Among the nearly one hundred active ingredients in cannabis plants, CBD differs from the well-known tetrahydrocannabinol (THC) in that it does not produce euphoria, nor does it cause side effects such as dependence or abuse. According to current literature, cannabidiol (CBD) interacts with the human endocannabinoid system, primarily affecting the nervous system (e.g., related to brain plasticity, motor control, memory, cognition, stress, emotional responses, pain, learning, and memory). Therefore, CBD has potential benefits for neuroprotection and may even be effective in treating some intractable neurological disorders, such as refractory epilepsy (e.g., severe myoclonic epilepsy of infancy; Dravet syndrome and Lennox-Gastaut syndrome), schizophrenia, Parkinson's disease, and anxiety disorders. Furthermore, CBD also improves skin inflammation, has antioxidant properties, soothes sensitive and red skin, and enhances the skin's self-repairing ability; it can even be used to treat skin conditions such as eczema. Due to its potential for various therapeutic properties, as well as its good safety and tolerability, cannabidiol (CBD) is one of the most studied cannabis substances.

[0004] From a biopharmaceutical perspective, although cannabidiol (CBD) has a variety of beneficial pharmacological effects, and the skin is one of the drug delivery routes, although it is generally believed that small molecule drugs can easily penetrate the outermost stratum corneum of the skin, CBD itself is lipid-soluble and has poor aqueous solubility and poor permeability. This results in low CBD delivery efficiency, which in turn affects transdermal absorption and reduces the bioavailability of CBD, thus limiting the therapeutic effect.

[0005] In view of this, there is an urgent need in the field for a novel cannabidiol formulation to enhance its bioavailability and thereby reduce the dosage required by an improved drug delivery system. Summary of the Invention

[0006] The following is a brief summary of the invention to provide the reader with a basic understanding. This summary is not intended to be a broad generalization of the invention, nor is it intended to identify key / determining components of the invention or to outline its scope. Its sole purpose is to present certain concepts of the invention in a simplified form as a prelude to a more detailed description that follows.

[0007] In view of the needs in this field, the inventors of this invention have researched and analyzed existing compositions and their preparation methods in order to develop better compositions containing cannabidiol (CBD), particularly nanoparticle pharmaceutical compositions containing CBD, wherein the effective average particle size of the nanoparticles is less than about 1500 nm; preferably, the effective average particle size is about 100-600 nm; more preferably, the effective average particle size is about 100-550 nm; and even more preferably, the effective average particle size is about 100-300 nm. According to certain operational embodiments of the present invention, the effective average particle size of the nanoparticles is about 207.2-412.3 nm, and its polydispersity index (PDI) is about 0.206-0.766. According to a specific operational embodiment of the present invention, the effective average particle size of the nanoparticles is about 207.2 nm, and its polydispersity index is about 0.392. Furthermore, the cannabidiol composition exhibits excellent storage stability, maintaining good dispersibility without any stratification; and the resulting product is not prone to discoloration.

[0008] As implemented and extensively described herein, one aspect of the invention relates to a cannabidiol-containing patch comprising a support and an adhesive layer bonded to the support, wherein...

[0009] The colloidal layer comprises cannabidiol, a core material, a solubilizing and stabilizing material, and a gelling material. The cannabidiol, the core material, and the solubilizing and stabilizing material together form a multi-layered lipid nanoparticle. The ratio of cannabidiol:core material:solbilizing and stabilizing material:gelling material is approximately 1:1.6-16:17.4-183:30-300 (by weight).

[0010] The core material contains a lipid, which is composed of a solid lipid and a liquid lipid, wherein the ratio of the solid lipid to the liquid lipid is approximately 1:0.25-1.5 (by weight).

[0011] The solubilizing and stabilizing material comprises water and a first surfactant; and

[0012] The content of cannabidiol is approximately 0.2-2% (by weight) of the total mass of the colloidal layer.

[0013] According to a specific embodiment of the present invention, in the colloidal layer of the patch of the present invention, the ratio of cannabidiol, the core material, the solubilizing and stabilizing material and the gelling material is approximately 1:13.3:152.3:250 (weight ratio); in the core material, the ratio of solid lipids to liquid lipids is approximately 1:1.5 (weight ratio); and the content of cannabidiol accounts for approximately 0.24% (weight ratio) of the total mass of the colloidal layer.

[0014] According to certain embodiments of the present invention, the core material of the patch of the present invention may further include a first antioxidant, a second surfactant, or a combination of the first antioxidant and the second surfactant; and the solubilizing and stabilizing material of the patch of the present invention may further include an alcohol, a second antioxidant, or a combination of the alcohol and the second antioxidant.

[0015] According to certain embodiments of the present invention, in the patch of the present invention, the solid lipids used may be glyceryl dibehenate, cocoa butter, or combinations thereof; the liquid lipids may be castor oil, rosehip oil, oleic acid, triglycerides, squalane, or combinations thereof, or other solid and liquid lipids that can achieve the same effect, or any combination of the above-mentioned solid and liquid lipids; the alcohols may be ethanol, 2-(2-ethoxyethoxy)ethanol, or polyethylene glycol 200-600. The first or second antioxidant may be the same or different, for example, it may be uric acid, N-acetylcysteine, sodium bisulfite, sodium metabisulfite, ethylenediaminetetraacetic acid (EDTA), ascorbic acid (vitamin C), glutathione, melatonin, tocofersolan, α-tocopherol, tocopheryl acetate, or other antioxidants that achieve the same effect, or any combination of the above-mentioned antioxidants; and the first or second surfactant may be cholesterol, lecithin, poloxamer, polyglyceryl-10 oleate, polyoxyethylene-40 hydrogenated castor oil, polysorbate 80, etc. 80), or other surfactants that can achieve the same effect, or any combination of the above types of surfactants.

[0016] According to a preferred embodiment of the present invention, the core material of the patch of the present invention is composed of the lipids, the first antioxidant and the second surfactant, wherein the lipids are composed of the solid lipid disorbate and the liquid lipid triglyceride, the first antioxidant is tococelen and the second surfactant is poloxamer; and the solubilizing and stabilizing material of the patch of the present invention is composed of water and the first surfactant, wherein the first surfactant is polysorbate 80.

[0017] According to a specific embodiment of the present invention, the core material of the patch of the present invention is composed of the lipid, the first antioxidant and the second surfactant in a ratio of about 1:0.2:0.4 (weight ratio), wherein the lipid is composed of the solid lipid disorbate and the liquid lipid triglyceride in a ratio of about 1:1.5 (weight ratio), the first antioxidant is tococelen and the second surfactant is poloxamer; and the solubilizing and stabilizing material of the patch of the present invention is composed of the water and the first surfactant in a ratio of about 1:0.01 (weight ratio), wherein the first surfactant is polysorbate 80.

[0018] According to certain embodiments of the present invention, the adhesive layer of the patch of the present invention is formed via the following steps:

[0019] (1) The cannabidiol and the core material are mixed in a ratio of approximately 1:1.6-16 (by weight) to form a first mixture;

[0020] (2) The first mixture from step (1) is mixed with the solubilizing stabilizer at a ratio of about 1:6.7-10.8 (by weight) to form a second mixture;

[0021] (3) The second mixture from step (2) is mixed with the gelling material in a ratio of about 1:1.5 (by weight) to form a third mixture;

[0022] (4) The third mixture from step (3) is cured to form the colloidal layer;

[0023] In this core material, the solid lipid and the liquid lipid are mixed in a ratio of approximately 1:0.25-1.5 (by weight).

[0024] According to a specific embodiment of the present invention, the adhesive layer of the patch of the present invention is formed via the following steps:

[0025] (1) The cannabidiol and the core material are mixed in a ratio of approximately 1:13.3 (by weight) to form a first mixture;

[0026] (2) The first mixture from step (1) is mixed with the solubilizing stabilizer at a ratio of about 1:10.6 (by weight) to form a second mixture;

[0027] (3) The second mixture from step (2) is mixed with the gelling material in a ratio of about 1:1.5 (by weight) to form a third mixture;

[0028] (4) The third mixture from step (3) is cured to form the colloidal layer;

[0029] In this core material, the solid lipid and the liquid lipid are mixed in a ratio of approximately 1:1.5 (by weight).

[0030] According to certain embodiments of the present invention, in step (4) of forming the colloidal layer of the patch of the present invention, the colloidal layer is cured by irradiation with ultraviolet light (UV), and the gelling material comprises a hydrophilic monomer, a crosslinking agent, and a photoinitiator, wherein...

[0031] The hydrophilic monomers are allyl methacrylate (AMA), 2-acrylamido-2-methylpropanesulfonic acid (AMPS), cellulose acetate butyrate (CAB), cyclohexyl methacrylate (CMA), diacetone acrylamide (DAA), fluoro-siloxy methacrylate (FSA), N-formylmethylacrylamide (FMA), glyceryl methacrylate (GMA), hydroxyethyl methacrylate (HEMA), isobutyl methacrylate (IBMA), methacrylate (MAA), N,N-dimethylacrylamide (DMA), and N-vinylpyrrolidone (N-vinyl... pyrrolidone (NVP), poly(ethylene glycol) diacrylate, poly(methyl methacrylate) (PMMA), poly(N-vinyl pyrrolidone) (PVP), siloxy methacrylate (SMA), triethyleneglycol dimethacrylate (TEGDMA) or combinations thereof;

[0032] The crosslinking agent is tetraethyleneglycol diacrylate, triethyleneglycol diacrylate, ethyleneglycol diacrylate, diethyleneglycol diacrylate, tetraethyleneglycol dimethacrylate, triethyleneglycol dimethacrylate, ethyleneglycol dimethacrylate, diethyleneglycol dimethacrylate, trimethylopropane trimethacrylate, pentaerythritol tetramethacrylate, bisphenol A dimethacrylate, vinyl methacrylate, ethylenediamine dimethyacrylamide, ethylenediamine dimethyacrylamide, and glycerol dimethacrylate. dimethacrylate), triallyl isocyanurate, triallyl cyanurate, allyl methacrylate, allyl methacrylate, 1,3-bis(methacrylamidopropyl)-1,1,3,3-tetrakis(trimethylsiloxy)disiloxane, N,N'-methylenebisacrylamide (NMBA), N,N'-methylenebismethacrylamide, N,N'-ethylenebisacrylamide, N,N'-ethylenebisacrylamide, N,N'-ethylenebismethacrylamide, 1,3-bis(N-methacrylamidopropyl)-1,1,3,3-tetrakis-(trimethylsiloxy)disiloxane, 1,3-bis(methacrylamidopropyl)-1,1,3,3-tetrakis-(trimethylsiloxy)disiloxane, 1,3-bis(methacrylamidobutyl)-1,1,3,3-tetrakis-(trimethylsiloxy)disiloxane ethylsiloxy)-disiloxane, 1,3-bis(acrylamidopropyl)-1,1,3,3-tetrakis(trimethylsiloxy)disiloxane, 1,3-bis(methacryloxyethylureidopropyl)-1,1,3,3-tetrakis(trimethylsiloxy)disiloxane, trimethylolpropanetrimethacrylate (TMPTMA), or combinations thereof; and,

[0033] The photoinitiator is benzoin methyl ether, diethoxyacetophenone, 2,4,6-trimethylbenzoyldiphenylophosphine oxide, bis-(2,6-dichlorobenzoyl)-4-N-propylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-4-N-butylphenylphosphine oxide, 1-hydroxycyclohexyl phenyl ketone, or 2-hydroxy-2-methyl propiophenone (HMPP).

[0034] According to a preferred embodiment of the present invention, in the adhesive material of the patch cured by ultraviolet light, the monomer is composed of 2-acrylamido-2-methylpropanesulfonic acid (AMPS) and hydroxyethyl methacrylate (HEMA), the crosslinking agent is N,N'-methylenebisacrylamide (NMBA), the photoinitiator is 2-hydroxy-2-methylphenylacetone (HMPP), and the ratio of AMPS:HEMA:NMBA:HMPP is approximately 1:0.01-1:0.01-0.5:0.01-0.5 (by weight). In a specific operational embodiment, the ratio of AMPS:HEMA:NMBA:HMPP in the adhesive material of the patch cured by ultraviolet light is approximately 1:0.07:0.02:0.02 (by weight).

[0035] According to certain embodiments of the present invention, in step (4) of forming the colloidal layer of the patch of the present invention, the colloidal layer is cured by irradiation with ultraviolet light, and the third mixture of step (3) is irradiated with 400 watts of ultraviolet light for about 5 to 60 seconds.

[0036] According to certain embodiments of the present invention, in the step of forming the colloidal layer of the patch of the present invention, steps (3) and (4) are replaced with the following steps:

[0037] (3-1) The second mixture from step (2) is used to soak the gelling material at a ratio of approximately 1:0.003-0.007 (by weight) to form the colloidal layer; wherein the gelling material absorbs approximately 10-80% of the weight of the second mixture, and the gelling material is a silicone-containing hydrogel, which is polymerized from a silicone-containing ethylene monomer.

[0038] The silicon-containing ethylene monomers are polydimethylsiloxane (PDMS), N-[tris(trimethylsiloxy)silylpropyl]acrylamide, N-[tris(trimethylsiloxy)silylpropyl]methacrylamide, tristrimethylsilyloxysilylpropyl methacrylate (TRIS), methacryloxyalkylsiloxane, 3-methacryloxypropylpentamethyldisiloxane, bis(methacryloxypropyl)tetramethyl-disiloxane, and monomethacrylated polydimethylsiloxane. Polydimethylsiloxane, monoacrylated polydimethylsiloxane, mercapto-terminated polydimethylsiloxane, or combinations thereof.

[0039] According to a preferred embodiment of the present invention, the silicone-containing hydrogel adhesive of the patch of the present invention is composed of polydimethylsiloxane (PDMS), 2-hydroxy-2-methylphenylacetone (HMPP), and trimethylolpropane trimethacrylate (TMPTMA). According to a specific embodiment of the present invention, the silicone-containing hydrogel adhesive of the patch of the present invention is composed of polydimethylsiloxane, 2-hydroxy-2-methylphenylacetone, and trimethylolpropane trimethacrylate in a ratio of approximately 1:0.14:0.01 (by weight).

[0040] According to certain embodiments of the present invention, in step (4) of forming the colloidal layer of the patch of the present invention, the colloidal layer is cured by heating, and the gelling material is composed of at least one material selected from the group consisting of water, 1,3-butanediol, carboxymethyl cellulose, carboxyvinyl polymer, diethylene glycol, ethylene glycol, glycerin, hydroxyethyl cellulose, malic acid, poloxamer, polyethylene glycol, polypropylene glycol, polyvinyl alcohol, polyvinylpyrrolidone, and sorbitol.

[0041] According to a preferred embodiment of the present invention, the thermosetting adhesive material of the patch of the present invention is composed of water, glycerin, malic acid, polyvinyl alcohol, polyvinyl carboxylate, carboxymethyl cellulose, and hydroxyethyl cellulose. In a specific operational embodiment, the thermosetting adhesive material of the patch of the present invention is composed of 63.5% (by weight) water, 15% (by weight) glycerin, 8.5% (by weight) malic acid, 7% (by weight) polyvinyl alcohol, 3.2% (by weight) polyvinyl carboxylate, 1.4% (by weight) carboxymethyl cellulose, and 1.4% (by weight) hydroxyethyl cellulose.

[0042] According to a preferred embodiment of the present invention, the effective average particle size of the multi-shell lipid nanoparticles of the patch of the present invention is about 100-1500 nanometers; more preferably, the effective average particle size of the multi-shell lipid nanoparticles is about 100-600 nanometers; even more preferably, the effective average particle size of the multi-shell lipid nanoparticles is about 100-300 nanometers.

[0043] Many of the accompanying features and advantages of the present invention will become readily apparent upon reading the following detailed description and accompanying drawings. Attached Figure Description

[0044] The invention and its other features, aspects, and advantages will become more apparent and understandable after referring to the following detailed description, claims, and drawings, wherein...

[0045] Figure 1 The results of high-performance liquid chromatography (HPLC) analysis obtained according to an embodiment of the present invention compare the purity of cannabidiol (experimental sample; small figure A) in the patch of the present invention with that of commercially available cannabidiol (reference sample; small figure B).

[0046] Figure 2 This is a particle size distribution diagram of nanoparticles obtained according to an embodiment of the present invention. Detailed Implementation

[0047] To make the description of this invention more detailed and complete, illustrative descriptions of embodiments and specific examples of this invention are provided below; however, these are not the only forms of implementing or utilizing the specific examples of this invention. The embodiments cover features of multiple specific examples and the methods, steps, and their order for constructing and operating these specific examples. However, other specific examples may also be used to achieve the same or equivalent functions and sequence of steps.

[0048] I. Definition

[0049] For convenience, specific proper nouns used in this specification, embodiments, and appended claims are concentrated herein. Unless otherwise defined herein, the scientific and technical terms used herein have the same meaning as understood and commonly used by one of ordinary skill in the art to which this invention pertains. Furthermore, where the context does not conflict, the singular noun used herein shall encompass the plural form of the noun, and the plural noun used herein shall encompass the singular form of the noun. Specifically, in this specification and claims, the singular form “a” (a and an) includes the plural reference value, unless otherwise indicated by the context. Furthermore, in this specification and claims, the expressions “at least one” and “one or more” have the same meaning, both representing a total of one, two, three, or more.

[0050] While the numerical ranges and parameters used to define the broader scope of this invention are approximate values, the relevant values ​​in the specific embodiments have been presented as precisely as possible. However, any value inevitably contains standard deviations due to individual testing methods. Here, "approximately" generally means that the actual value is within plus or minus 10%, 5%, 1%, or 0.5% of a particular value or range. Alternatively, the term "approximately" may mean that the actual value falls within the acceptable standard error of the average, as determined by those skilled in the art. Except for experimental examples, or unless explicitly stated otherwise, it is understood that all ranges, quantities, values, and percentages used herein (e.g., to describe material usage, duration, temperature, operating conditions, quantity ratios, and the like) are modified with "approximately". Therefore, unless otherwise stated, the numerical parameters disclosed in this specification and the accompanying claims are approximate values ​​and are subject to change as needed. At a minimum, these numerical parameters should be understood as the indicated significant digits and values ​​obtained by applying general rounding.

[0051] As used herein, the term "core material" refers to a material primarily composed of lipid components, which is miscible with lipophilic pharmaceutical active ingredients (e.g., cannabidiol of the present invention), and may be used in combination with antioxidants and / or surfactants, depending on the circumstances, to constitute the core material. The term "lipids" encompasses both "solid lipids" and "liquid lipids," wherein solid lipids refer to lipids that are solid at room temperature (25-28°C), for example, those with a single carbon chain having 12 or more carbon atoms; and liquid lipids refer to lipids that are liquid at room temperature (25-28°C).

[0052] As used herein, the term "solution-stabilizing material" refers to a material primarily composed of water and surfactants, with the addition of alcohols and / or antioxidants as needed. This material can be used to increase the permeability of physiological barriers (e.g., skin, viscera, muscles, eyes, etc.) to pharmaceutical active ingredients, thereby increasing the rate at which the active pharmaceutical ingredient permeates through these barriers and enters the bloodstream. By using a solution-stabilizing material (e.g., by using the compositions of the present invention), enhanced penetration of the active pharmaceutical ingredient can be achieved, and this can be observed, for example, by measuring the diffusion rate of the drug in vitro (e.g., using animal or human skin using a diffusion cell device) or in vivo.

[0053] As used herein, the term “gelling material” refers to a polymerizable composition or material or matrix-forming material that can be cured (e.g., crosslinked and / or polymerized) by physical (e.g., ionic / electrostatic interactions, hydrogen bonding, physical stacking (heating), metal coordination, etc.) or chemical (e.g., photochemical radiation (e.g., ultraviolet radiation, ionizing radiation (e.g., gamma-ray or X-ray radiation), microwave radiation and similar radiation), or enzyme catalysis, etc.) action.

[0054] In this invention, the term "monomer" refers to a molecule containing one or more polymerizable functional groups prior to polymerization, and a repeating unit of a polymer. More specifically, the term "monomer" refers to any molecule capable of polymerization that can be chemically linked together to form a molecule with a higher molecular weight. A "copolymer" is a molecule containing two or more different monomers.

[0055] In this invention, the term "crosslinking agent" refers to a compound capable of forming stable covalent bonds. More specifically, the term "crosslinking agent" includes any molecule or atom capable of forming one or more crosslinks between molecules of a crosslinked polymer, and / or between two or more atoms in a single molecule of a crosslinked polymer. The term "crosslink" in this invention refers to a covalent bond used to connect a polymer chain to another polymer chain.

[0056] In this invention, the term "photoinitiator" refers to a photosensitive chemical substance that undergoes a chemical change upon photochemical radiation (e.g., light of a suitable wavelength, specifically ultraviolet light), decomposing into free radicals or cations to trigger polymerization, i.e., further initiating a chemical chain reaction with polymer monomers to generate a high molecular weight polymer. Furthermore, specific spectral wavelengths can be controlled by adding appropriate photosensitizers as needed.

[0057] In this invention, the term "effective average particle size less than about 1500 nanometers" means that when the effective average particle size (Z-average) is determined using dynamic light scattering (DLS) or other methods well known in the art, at least about 50% of the multi-shell lipid nanoparticle composition containing cannabidiol has a particle size of less than about 1500 nanometers. The dynamic light scattering instrument used in this invention (Zetasizer Nano ZS90; Malvern Instruments Ltd.) utilizes a laser to strike a solution containing particles. When the laser strikes the particles, it generates scattered light, which changes over time. Therefore, the particle size distribution is calculated by measuring the scattered light.

[0058] In this invention, the term "polydispersity index" (PDI) is commonly used in the determination of particle size or molecular weight of polymers. It refers to an index describing whether particles are uniformly distributed. The PDI value is between 0 and 1. That is, the smaller the PDI value, the higher the uniformity of the particles, and the more they tend to be monodisperse. In other words, the larger the PDI value, the lower the uniformity of the particles, and the more they tend to be polydisperse.

[0059] As used herein, the term "penetration of physiological barriers" generally refers to the delivery of a drug's active ingredient (e.g., cannabidiol) across physiological barriers (e.g., skin, internal organs, muscles, eyes, etc.). For example, the term "transdermal" can refer to the delivery of a drug's active ingredient to a local tissue or the systemic circulatory system through the skin without actually cutting or penetrating the skin (e.g., cutting with a scalpel or puncturing the skin with a hypodermal syringe needle). The term "transdermal delivery" refers to drug delivery across the skin, typically accomplished without damaging the skin, including delivery via passive diffusion.

[0060] The terms "subject" or "patient" refer to an animal, including humans, that can be treated with the patch of the present invention. Unless otherwise specified, the terms "subject" and "patient" refer to both males and females. Accordingly, the terms "subject" and "patient" encompass any mammal that can benefit from the application of the patch of the present invention. Examples of "subjects" and "patients" that can be treated with the patch of the present invention include, but are not limited to, humans, rats, mice, guinea pigs, monkeys, pigs, goats, dairy cows, horses, dogs, cats, birds, and chickens. In one illustrative embodiment, the subject is a human.

[0061] II. Detailed Description of the Invention

[0062] This invention covers a pharmaceutical composition for delivering a pharmaceutically active ingredient across physiological barriers (e.g., transdermal delivery) to an individual, particularly a patch containing cannabidiol (CBD). The patch contains a dosage form of CBD-containing multi-shell lipid nanoparticles, which can penetrate physiological barriers within an individual with a water content of approximately 10-99% (e.g., skin (water content approximately 10-80%), internal organs (water content approximately 68-83%), muscles (water content approximately 70-75%), and eyes (water content approximately 90-99%). The CBD-containing multi-shell lipid nanoparticle dosage form has a uniform particle size distribution, is not easily affected by environmental changes, and exhibits stable properties. This invention's patch containing nano-sized CBD, through the formulation of a specific ratio of solid and liquid lipids, significantly improves drug delivery / release efficiency while maintaining dosage stability (preventing oil-water separation), thereby enhancing bioavailability and achieving the goal of reducing the dosage.

[0063] Cannabidiol-containing patches

[0064] One aspect of the present invention aims to provide a patch for delivering cannabidiol (CBD) across physiological barriers (e.g., transdermal delivery) to an individual, the patch comprising a support and a gel layer adhered to the support, wherein...

[0065] The colloidal layer comprises cannabidiol, a core material, a solubilizing and stabilizing material, and a gelling material. The cannabidiol, the core material, and the solubilizing and stabilizing material together form a multi-shell lipid nanoparticle. The ratio of cannabidiol:core material:solbilizing and stabilizing material:gelling material is approximately 1:1.6-16:17.4-183:30-300 (by weight).

[0066] The core material contains a lipid, which is composed of a solid lipid and a liquid lipid.

[0067] The solubilizing and stabilizing material comprises water and a first surfactant; and

[0068] The content of cannabidiol is approximately 0.2-2% (by weight) of the total mass of the colloidal layer.

[0069] The patches described in this invention, particularly those for transdermal delivery, can be single-layer adhesive patches, multi-layer adhesive patches, reservoir patches, matrix patches, microneedle patches, or iontophoresis patches requiring the application of direct current. In some embodiments, the patches of this invention can be used for continuous release. In some embodiments, the patches of this invention may rely on passive chemical diffusion rather than methods based on physical, electrical, or mechanical principles. For example, a passive transdermal patch may have a drug reservoir containing a high concentration of drug for contact with the skin, wherein the drug diffuses through the skin and enters the body tissues or bloodstream of an individual.

[0070] The patch of the present invention can be manufactured using methods known in the art for manufacturing patches. For example, the aforementioned colloidal layer can be stretched onto a support (first support), and, if necessary, the surface of the colloidal layer can be covered with another support (second support) of the same or different material, thereby forming the patch of the present invention. The support can be made of stretchable or non-stretchable materials commonly used in patches. Specifically, it can be a film or sheet formed from polyesters such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; polyolefins such as polyethylene, polypropylene, and polybutadiene; synthetic resins such as ethylene vinyl acetate polymers, polyvinyl chloride, nylon, polyurethane, cellulose derivatives, and polyacrylonitrile, or synthetic resins such as cotton, or such laminates, porous membranes, foams, woven and non-woven fabrics, porous membranes, foams, paper, etc.

[0071] The cannabidiol (CBD) in the patch of the present invention may be derived from cannabis extract or cannabinoids therein; preferably, the CBD used in the patch of the present invention does not contain tetrahydrocannabinol (THC), or the THC content is less than 0.24% (by weight) of the total weight of the patch of the present invention. Furthermore, the CBD in the patch of the present invention accounts for approximately 0.2-2% (by weight) of the total mass of the gel layer; preferably, the CBD accounts for approximately 0.2-1% (by weight) of the total mass of the gel layer; more preferably, the CBD accounts for approximately 0.2-0.5% (by weight) of the total mass of the gel layer. According to a specific embodiment of the present invention, the CBD accounts for approximately 0.2% (by weight) of the total mass of the gel layer. According to other embodiments of the present invention, the CBD accounts for approximately 0.24% (by weight) of the total mass of the gel layer. According to other embodiments of the present invention, the CBD accounts for approximately 0.8% (by weight) of the total mass of the gel layer. According to other embodiments of the present invention, the cannabidiol accounts for approximately 2% (by weight) of the total mass of the colloidal layer.

[0072] According to certain embodiments of the present invention, the water used in the patch of the present invention can be any type of purified water, such as deionized water, distilled water, demineralized water, or pure water; or water containing minerals or salts, such as tap water or mineral water. In a specific embodiment, the water used to formulate the patch of the present invention is deionized water.

[0073] According to certain embodiments of the present invention, the lipids in the patch of the present invention are composed of a solid lipid and a liquid lipid, wherein the ratio of the solid lipid to the liquid lipid can be 1:0.1-10 (by weight). For example, the ratio of the solid lipid to the liquid lipid can be 1:0.1, 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4, 1:0.45, 1:0.5, 1:0.55, 1:0.6, 1:0.65, 1:0.7, 1:0.75, 1:0.8, 1:0.85, 1:0.9, 1:0.95, 1:1, 1:1, 1:1.25, 1:1.5, 1:1.75, 1:2, 1:2.25, 1:2.5. 1:2.75, 1:3, 1:3.25, 1:3.5, 1:3.75, 1:4, 1:4.25, 1:4.5, 1:4.75, 1:5, 1:5.25, 1:5.5, 1:5.75, 1:6, 1:6.25, 1:6.5, 1:6.75, 1:7, 1:7.25, 1:7.5, 1:7.75, 1:8, 1:8.25, 1:8.5, 1:8.75, 1:9, 1:9.25, 1:9.5, 1:9.75, 1:10 (weight ratio). According to some embodiments of the present invention, the ratio of solid lipid to liquid lipid is approximately 1:0.25-1.5 (weight ratio). According to a preferred embodiment of the present invention, the ratio of solid lipid to liquid lipid is approximately 1:1-5 (weight ratio). According to a preferred embodiment of the present invention, the ratio of the solid lipid to the liquid lipid is approximately 1:1-3 (by weight). In a specific embodiment, the ratio of the solid lipid to the liquid lipid is approximately 1:1.5 (by weight). In another specific embodiment, the ratio of the solid lipid to the liquid lipid is approximately 1:0.25 (by weight).

[0074] According to certain embodiments of the present invention, the solid lipids in the patch of the present invention may be cocoa butter, coconut oil, hydrogenated cottonseed oil, hydrogenated palm kernel oil, palm kernel oil, lauric acid, linoleic acid, palmitic acid, stearic acid, stearyl alcohol, lauryl alcohol, myristyl alcohol, behenyl alcohol, propylene glycol laurate, methyl laurate, propylene glycol monolaurate, or propylene glycerol dilaurate. Dilaurate, glyceryl monolaurate, glyceryl monooleate, glyceryl disorbate, sorbitan monooleate, isopropyl palmitate, sorbitan monolaurate, isopropyl n-decanoate, octyl dodecyl myristate, pure ceresin, natural ceresin, paraffin wax, polyethylene wax, microcrystalline wax, beeswax, candelilla wax, cotton wax, carnauba wax, cetacean wax, lauryl wax, insect wax, cetacean wax, lignite wax, rice bran wax, lanolin, kapok wax, lanolin acetate, liquid lanolin, sugarcane wax, lanolin fatty acid isopropyl ester, hexyl laurate, reduced lanolin, jojoba wax, hard lanolin, shellac wax, and mixtures thereof, in any proportion.The liquid lipids include, but are not limited to, macadamia nut oil, jojoba oil, egg yolk oil, sesame oil, soybean oil, rice bran oil, germ oil, citrus oil, olive oil, avocado oil, almond oil, babassu oil, borage oil, camellia oil, canola oil, castor oil, corn oil, cottonseed oil, emu oil, evening primrose oil, maleic acidified soybean oil, meadowfoam seed oil, peanut oil, rapeseed oil, grapeseed oil, safflower oil, sphingolipids, seed almond oil, tall oil, linoleic acid, rosehip oil, calendula oil, chamomile oil, eucalyptus oil, juniper berry oil, and sandalwood. Wood oil, tea tree oil, sunflower oil, soybean oil, squalane, oleic acid, alkanonic acid, decanoic acid, hexanoic acid, lactic acid, ethyl oleate, methyl propionate, monoglyceride, triglycerides, liquid paraffin, polybutene, isocetyl isostearate, ethylene glycol di-2-ethylhexanoate, cetyl 2-ethylhexanoate, trimethylolpropane tri-2-ethylhexanoate, pentaerythritol tetra-2-ethylhexanoate, tri-2-heptylundecanoate, diisobutyl adipate, 2-hexyldecyl sebacate, tricaprylic acid, triisopalmitoate, apple Diisostearyl glycolate, isopropyl myristate, 2-octyl dodecyl oleate, hexyl decyl dimethyl octanoate, 2-hexyl decyl myristate, myristyl myristate, octyl dodecyl myristate, isopropyl palmitate, 2-ethylhexyl palmitate, 2-hexyl decyl palmitate, 2-heptyl undecyl palmitate, butyl stearate, isocetyl stearate, decyl oleate, dodecyl oleate, oleyl oleate, myristyl lactate, cetyl lactate, 12-hydroxystearic acid cholesterol ester, castor oil Methyl fatty acid esters, 2-ethylhexyl succinate, 2-hexyldecyl adipate, di-2-heptylundecyl oxalate, diisopropyl sebacate, di-2-ethylhexyl sebacate, neopentyl glycol didecanoate, neopentyl glycol dioctanoate, tri-2-ethylhexanoate, trimyristic acid glyceride, tri-2-heptylundecanoate, trimethylolpropane triisostearate, polydimethylsiloxane, polymethylphenylsiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, and mixtures thereof, combined in any proportion. According to a preferred embodiment of the invention, the lipids used in the patch of the invention are: solid lipids are diglyceride dibehenate, cocoa butter, and combinations thereof; and liquid lipids are castor oil, rosehip oil, oleic acid, triglycerides, squalane, and combinations thereof.

[0075] According to certain embodiments of the present invention, the alcohols in the patch of the present invention refer to saturated or unsaturated, branched or unbranched C2-C molecules functionalized with at least two hydroxyl (-OH) groups. 60 C2-C 30 Or C2-C 20The carbon chain can be ethanol, 2-(2-ethoxyethoxy)ethanol, propylene glycol, butanediol, polyethylene glycol (such as polyethylene glycol 200-600), ethylene glycol, diethylene glycol, triethylene glycol, dipropylene glycol, ethoxydiethylene glycol, pentanediol, glycerin, propanediol, butanediol, pentanediol, sorbitol, sucrose, mannitol, trehalose, glycerol, and glycerin, etc. According to a preferred embodiment of the invention, the alcohol used in the patch of the invention is selected from the group consisting of ethanol, 2-(2-ethoxyethoxy)ethanol, polyethylene glycol 200-600, propylene glycol, glycerin, and combinations thereof.

[0076] According to certain embodiments of the present invention, examples of antioxidants in the patch of the present invention include uric acid, N-acetylcysteine, sodium bisulfite, sodium metabisulfite, ethylenediaminetetraacetic acid (EDTA), ascorbic acid, glutathione, melatonin, tococelen, α-tocopherol, tocopheryl acetate, or combinations thereof. According to a preferred embodiment of the present invention, the antioxidant used in the patch of the present invention is selected from the group consisting of tococelen, α-tocopherol, tocopheryl acetate, and combinations thereof.

[0077] According to certain embodiments of the present invention, the surfactants suitable for use in the patches of the present invention may include anionic surfactants, cationic surfactants, nonionic surfactants, bile salts, and lecithin, etc. Examples of suitable anionic surfactants include sodium lauryl sulfate, sodium lauryl sulfate, and sodium laureth sulfate. Suitable cationic surfactants include hexadecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, benzalkonium chloride, octadecyltrimethylammonium chloride, hexadecylpyridine chloride, dodecyltrimethylammonium chloride, and hexadecyltrimethylammonium chloride. Examples of suitable nonionic surfactants include poloxamer (such as poloxamer 231, poloxamer 182, poloxamer 184), 30 (polyoxyethylene (4) lauryl ether), 93 (polyoxyethylene (2) oleyl ether), 96 (polyoxyethylene (20) oleyl ether), 99 (polyoxyethylene (10) oleyl ether), 20 (sorbitan monolaurate), 40 (sorbitan monopalmitate), 60 (sorbitan monostearate), 80 (sorbitan monooleate; polysorbate 80), 85 (sorbitan trioleate), and 20 (polyethylene glycol sorbitan monolaurate). Esters; polyoxyethylene (20) sorbitol monolaurate), 40 (polyoxyethylene (20) sorbitol monopalmitate), 60 (polyethylene glycol sorbitol monostearate; polyoxyethylene (20) sorbitol monostearate), 80 (polyethylene glycol sorbitol monooleate; polyoxyethylene (20) sorbitol monooleate), 45 (polyoxyethylene (8) stearate), 51 (polyoxyethylene stearate), 52 (polyoxyethylene stearate), propylene glycol dicaprylate / dicaprylate, glyceryl disorbate, polyglycerol-10 oleate, polyethylene glycol-40 hydrogenated castor oil, etc. Examples of suitable bile salts include sodium cholate and sodium salts of taurocholic acid, glycolic acid, deoxycholic acid, and cholesterol. According to a preferred embodiment of the present invention, the surfactant used in the patch of the present invention is selected from the group consisting of cholesterol, lecithin, poloxamer, polyglycerol-10 oleate, polyethylene glycol-40 hydrogenated castor oil, polysorbate 80, and combinations thereof.

[0078] According to embodiments of the present invention, the ratio of cannabidiol to the core material in the patch of the present invention is approximately 1:1.6-16 (by weight), for example, approximately 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:5.5, 1:6, 1:6.5, 1:7, 1:7.5, 1:8, The ratios of cannabidiol to the core material in the patch of the present invention are approximately 1:1.6 (by weight). In other embodiments, the ratio of cannabidiol to the core material in the patch of the present invention is approximately 1:4 (by weight). In other embodiments, the ratio of cannabidiol to the core material in the patch of the present invention is approximately 1:13.3 (by weight). In other embodiments, the ratio of cannabidiol to the core material in the patch of the present invention is approximately 1:13.3 (by weight). In other embodiments, the ratio of cannabidiol to the core material in the patch of the present invention is approximately 1:16 (by weight). According to a preferred embodiment of the present invention, the core material of the patch comprises a lipid. According to other preferred embodiments of the present invention, in addition to the lipid, the core material of the patch may further comprise a first antioxidant, a second surfactant, or a combination of the first antioxidant and the second surfactant in any proportion. For example, the core material of the patch may be a combination of the lipid and the first antioxidant in any proportion, a combination of the lipid and the second surfactant in any proportion, or a combination of the lipid, the first antioxidant, and the second surfactant in any proportion. The lipid and its formulation ratio, the first antioxidant, and the second surfactant have been described above and will not be repeated for the sake of brevity.

[0079] Furthermore, if the core material of the patch of the present invention uses one or more lipids (for example, using two lipids simultaneously (for example, the solid lipid disorbate and the liquid lipid triglyceride, or the solid lipid cocoa butter and the liquid lipid triglyceride), or using three lipids simultaneously (for example, the solid lipid disorbate and cocoa butter and the liquid lipid triglyceride, the solid lipid disorbate and the liquid lipid triglyceride and squalane ... The formulation may include a mixture of disorbate diglycerides and liquid triglycerides and rosehip oil, one or more antioxidants (e.g., tococelen and glutathione used simultaneously), or one or more surfactants (e.g., poloxamer and polysorbate 80 used simultaneously). The formulation ratios of the components of the one or more lipids are as described above, and the components of the one or more antioxidants or surfactants can still be combined in any proportion. According to some embodiments of the invention, the lipids in the core material are composed of two oils (e.g., the solid lipid cocoa butter and the liquid lipid triglycerides, or the solid lipid disorbate diglycerides and the liquid lipid triglycerides) in a ratio of approximately 1:0.25-1.5 (by weight). In one embodiment of the present invention, the core material of the patch is composed of the lipid, the first antioxidant, and the second surfactant in a ratio of about 1:0.2:0.4, wherein the lipid is composed of the solid lipid disorbate and the liquid lipid triglyceride in a ratio of about 1:1.5 (by weight), the first antioxidant is tococelen, and the second surfactant is poloxamer.

[0080] According to embodiments of the present invention, the ratio of cannabidiol to the solubilizing and stabilizing material in the patch of the present invention is approximately 1:17.4-183 (by weight). In one embodiment, the ratio of cannabidiol to the solubilizing and stabilizing material in the patch of the present invention is approximately 1:17.4 (by weight). In another embodiment, the ratio of cannabidiol to the solubilizing and stabilizing material in the patch of the present invention is approximately 1:45 (by weight). In another embodiment, the ratio of cannabidiol to the solubilizing and stabilizing material in the patch of the present invention is approximately 1:152.3 (by weight). In another embodiment, the ratio of cannabidiol to the solubilizing and stabilizing material in the patch of the present invention is approximately 1:183 (by weight). According to some embodiments of the present invention, the solubilizing and stabilizing material in the patch of the present invention comprises water and a first surfactant, and is composed of them in any proportion. According to other preferred embodiments of the present invention, in addition to water and the first surfactant, the solubilizing and stabilizing material in the patch of the present invention may further comprise an alcohol, a second antioxidant, or a combination of the alcohol and the second antioxidant in any proportion. For example, the solubilizing and stabilizing material in the patch of the present invention can be any combination of water, the first surfactant, and the alcohol in any proportion; or any combination of water, the first surfactant, the alcohol, and the second antioxidant in any proportion. The water, the alcohol, the second antioxidant, and the first surfactant described above are not repeated for the sake of brevity.

[0081] Furthermore, if the solubilizing and stabilizing material in the patch of the present invention uses one or more alcohols (e.g., 2-(2-ethoxyethoxy)ethanol and glycerin simultaneously), one or more antioxidants (e.g., tococelen and glutathione simultaneously), or one or more surfactants (e.g., poloxamer and polysorbate 80 simultaneously), then the components of the one or more alcohols, the one or more antioxidants, or the one or more surfactants can still be combined in any proportion. According to a specific embodiment of the present invention, the solubilizing and stabilizing material in the patch of the present invention is composed of water and the first surfactant in a ratio of approximately 1:0.006 (by weight).

[0082] According to embodiments of the present invention, the ratio of cannabidiol to the gelling material in the patch of the present invention is approximately 1:30-300 (by weight). In one embodiment, the ratio of cannabidiol to the solubilizing and stabilizing material in the patch of the present invention is approximately 1:30 (by weight). In another embodiment, the ratio of cannabidiol to the solubilizing and stabilizing material in the patch of the present invention is approximately 1:75 (by weight). In another embodiment, the ratio of cannabidiol to the solubilizing and stabilizing material in the patch of the present invention is approximately 1:250 (by weight). In yet another embodiment, the ratio of cannabidiol to the solubilizing and stabilizing material in the patch of the present invention is approximately 1:300 (by weight).

[0083] The colloidal layer in the patch of the present invention can be formed as a homogeneous or heterogeneous colloidal layer. According to certain embodiments of the present invention, the colloidal layer in the patch of the present invention is a homogeneous colloidal layer, and is formed through the following steps:

[0084] (1) The cannabidiol and the core material are mixed in a ratio of approximately 1:1.6-16 (by weight) to form a first mixture;

[0085] (2) The first mixture from step (1) is mixed with the solubilizing stabilizer at a ratio of about 1:6.7-10.8 (by weight) to form a second mixture;

[0086] (3) The second mixture from step (2) is mixed with the gelling material in a ratio of about 1:1.5 (by weight) to form a third mixture;

[0087] (4) The third mixture from step (3) is cured to form the colloidal layer;

[0088] The core material contains a lipid, which is composed of a solid lipid and a liquid lipid.

[0089] To form the homogeneous colloidal layer of the patch of the present invention, in step (1), the active pharmaceutical ingredient cannabidiol is mixed with the core material in a ratio of about 1:1.6-16 (by weight), for example, in ratios of about 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:5.5, 1:6, 1:6.5, 1:7, and 1:7. The mixture is prepared in a ratio of 5:1:8, 1:8.5, 1:9, 1:9.5, 1:10, 1:10.5, 1:11, 1:11.5, 1:12, 1:12.5, 1:13, 1:13.3, 1:13.5, 1:13.8, 1:14, 1:14.3, 1:14.5, 1:14.8, 1:15, 1:15.3, 1:15.5, 1:15.8, or 1:16 (by weight). In one embodiment, cannabidiol is mixed with the core material in a ratio of approximately 1:1.6 (by weight) to prepare the first mixture. In other embodiments, cannabidiol is mixed with the core material in a ratio of approximately 1:4 (by weight) to prepare the first mixture. In other embodiments, cannabidiol is mixed with the core material at a ratio of approximately 1:13.3 (by weight) to prepare the first mixture. In other embodiments, cannabidiol is mixed with the core material at a ratio of approximately 1:16 (by weight) to prepare the first mixture. The types and ratios of the solid and liquid lipids in the core material are as described above and will not be repeated for brevity. Alternatively, heating can be used to improve the uniform mixing of cannabidiol and the core material. For example, the core material can be preheated to its melting point of approximately 80-95°C to form a molten state. The melting point of the core material will vary depending on its composition and ratio. Then, cannabidiol is added to the molten core material, and heating and stirring are continued to achieve uniform dispersion and dissolution.

[0090] Next, in step (2), the first mixture obtained in step (1) is mixed with the solubilizing stabilizer at a ratio of approximately 1:6.7-10.8 (by weight). In one embodiment, the first mixture and the solubilizing stabilizer are mixed at a ratio of approximately 1:6.7 (by weight) to prepare the second mixture. In other embodiments, the first mixture and the solubilizing stabilizer are mixed at a ratio of approximately 1:9 (by weight) to prepare the second mixture. In other embodiments, the first mixture and the solubilizing stabilizer are mixed at a ratio of approximately 1:10.6 (by weight) to prepare the second mixture. In other embodiments, the first mixture and the solubilizing stabilizer are mixed at a ratio of approximately 1:10.8 (by weight) to prepare the second mixture. Optionally, the solubilizing stabilizer can be heated to facilitate uniform mixing with the first mixture. For example, the solubilizing stabilizer can be preheated to the melting point of the core material (80-95°C or about 10°C higher), and then the first mixture can be added to the solubilizing stabilizer to obtain the second mixture, which is maintained at 80-95°C. The second mixture is then emulsified and homogenized using a high-shear emulsifying homogenizer at a speed of about 3000-12000 rpm or a high-pressure homogenizer at a pressure of about 400-900 bar at a temperature of 80-95°C. The resulting homogenized second mixture contains a microstructure of multi-shell lipid nanoparticles. The homogenized second mixture is then rapidly cooled to room temperature. It is understood that the scope of the present invention covers compositions containing cannabidiol multi-shell lipid nanoparticles.

[0091] The composition of the present invention containing cannabidiol multi-shell lipid nanoparticles can be analyzed using measurement methods well known in the art. For example, the concentration of the active ingredient (such as cannabidiol) in the composition can be analyzed using a UV spectrophotometer, and the particle size of the multi-shell lipid nanoparticles in the composition can be analyzed using a dynamic light scattering (DLS) instrument.

[0092] Next, in step (3), the second mixture obtained in step (2) is further mixed with the gelling material at a ratio of approximately 1:1.5 (by weight). It is understood that the gelling material is used in conjunction with a gel curing method; for example, a gelling material for UV curing is used in conjunction with a UV curing method, and a gelling material for heat curing (such as a physical stack colloid) is used in conjunction with a heat curing method, and so on.

[0093] Finally, in step (4), the third mixture is cured using a curing method corresponding to the gelling material to form the colloidal layer. For example, if the colloidal curing method is ultraviolet curing, a 100-1000 watt (preferably 400 watt) ultraviolet lamp can be used to irradiate for about 5-60 seconds, for example, about 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, or 60 seconds; preferably, about 30-60 seconds. In a specific embodiment, the ultraviolet curing of the colloid is about 30 seconds, and a measured light intensity of about 1.68 joules per square centimeter can be obtained after 30 seconds of irradiation. It is worth noting that when the ultraviolet irradiation is longer than 60 seconds, the ultraviolet lamp is prone to generating high heat, which can cause the temperature to rise to about 55-65°C, and may cause the water in the colloid to evaporate and dissipate. According to the embodiments of the present invention, the concentration of unreacted monomers in the ultraviolet-cured colloid is finally measured to be less than 800 parts per million (ppm). For example, if the colloid curing method is a thermosetting method, the temperature can be adjusted to the critical temperature of the colloid material, which is approximately 50-100°C, for example, approximately 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, or 100°C, and heated for approximately 5-60 minutes, for example, approximately 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, or 60 minutes. The critical temperature of the colloid material will vary depending on its formulation and proportions. In one specific embodiment, the thermosetting colloid is heated at approximately 90°C for 20 minutes.

[0094] According to certain embodiments of the present invention, the colloidal layer is cured by irradiation with ultraviolet light; therefore, the gelling material is a gelling material for ultraviolet curing, comprising a hydrophilic monomer, a crosslinking agent, and a photoinitiator, wherein...

[0095] The hydrophilic monomer is allyl methacrylate, 2-acrylamido-2-methylpropanesulfonic acid, cellulose acetate butyrate, cyclohexyl methacrylate, diacetone acrylamide, fluorosiloxane methacrylate, N-formylmethacrylamide, glyceryl methacrylate, hydroxyethyl methacrylate, isobutyl methacrylate, methacrylate, N,N-dimethylacrylamide, N-vinylpyrrolidone, polyethylene glycol diacrylate, poly(methyl methacrylate), poly(N-vinylpyrrolidone), siloxane methacrylate, triethylene glycol dimethacrylate, or a combination thereof.

[0096] The crosslinking agent is tetraethylene glycol diacrylate, triethylene glycol diacrylate, ethylene glycol diacrylate, diethylene glycol diacrylate, tetraethylene glycol dimethacrylate, triethylene glycol dimethacrylate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, trimethylpropane trimethacrylate, isopentetrol tetramethacrylate, bisphenol A dimethacrylate, vinyl methacrylate, ethylenediamine dimethacrylamide, ethylenediamine diacrylamide, glycerol dimethacrylate, triallyl isocyanurate, triallyl cyanurate, allyl methacrylate, 1,3-bis(methacrylamidopropyl)-1,1,3,3-tetra(trimethylsiloxy)disiloxane, N N'-methylenebisacrylamide, N,N'-methylenebisacrylamide, N,N'-vinylbisacrylamide, N,N'-vinylbisacrylamide, 1,3-bis(N-methacrylamidopropyl)-1,1,3,3-tetra-(trimethylsilyloxy)disiloxane, 1,3-bis(methacrylamidopropyl)-1,1,3,3-tetra-(trimethylsilyloxy)disiloxane, 1,3-bis(acrylamidopropyl)-1,1,3,3-tetra-(trimethylsilyloxy)disiloxane, 1,3-bis(methacryloyloxyethylureapropyl)-1,1,3,3-tetra-(trimethylsilyloxy)disiloxane, trimethylolpropane trimethacrylate or combinations thereof; and

[0097] The photoinitiator is benzoin methyl ether, diethoxyacetophenone, 2,4,6-trimethylbenzoyl diphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-4-N-propylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-4-N-butylphenylphosphine oxide, 1-hydroxycyclohexylphenyl ketone, or 2-hydroxy-2-methylphenylacetone.

[0098] In a preferred embodiment of the present invention, the colloidal layer is cured by irradiation with ultraviolet light, and the monomer used in the gelling material is composed of 2-acrylamido-2-methylpropanesulfonic acid (AMPS) and hydroxyethyl methacrylate (HEMA), the crosslinking agent is N,N'-methylenebisacrylamide (NMBA), the photoinitiator is 2-hydroxy-2-methylphenylacetone (HMPP), and the ratio of AMPS:HEMA:NMBA:HMPP is approximately 1:0.01-1:0.01-0.5:0.01-0.5 (by weight). In one operational embodiment, the ratio of AMPS:HEMA:NMBA:HMPP in the gelling material is approximately 1:0.07:0.02:0.02 (by weight).

[0099] According to other embodiments of the present invention, the adhesive material in the patch of the present invention can be prepared by using the silicone-containing water-based adhesive as described above to prepare the colloidal layer in the patch of the present invention, wherein steps (3) and (4) above for preparing the colloidal layer are replaced by the following steps:

[0100] (3-1) The second mixture from step (2) is used to soak the gelling material at a ratio of about 1:0.003-0.007 (by weight) and soaked at room temperature for about 16-30 hours to form the colloidal layer; wherein the gelling material is a silicone-containing hydrogel, and wherein the silicone-containing hydrogel is polymerized from a silicone-containing ethylene monomer; wherein the silicone-containing ethylene monomer is polydimethylsiloxane, N-[tris(trimethylsiloxy)silylpropyl]acrylamide, N-[tris(trimethylsiloxy)silylpropyl]methacrylamide, tris(trimethylsiloxy)silylpropyl methacrylate, methacryloyloxyalkylsiloxane, 3-methacryloyloxypropylpentamethyldisiloxane, bis(methacryloyloxypropyl)tetramethyl-disiloxane, monomethacrylated polydimethylsiloxane, monoacrylated polydimethylsiloxane, mercapto-terminated polydimethylsiloxane or a combination thereof.

[0101] According to an embodiment of the present invention, the second mixture obtained in step (2) is used to soak the gelling material at a ratio of approximately 1:0.003-0.007 (weight ratio), for example, at a ratio of approximately 1:0.003, 1:0.004, 1:0.005, 1:0.006, or 1:0.007 (weight ratio). In a specific embodiment of the present invention, the second mixture from step (2) is used to soak the gelling material at a ratio of approximately 1:0.005 (weight ratio) for approximately 24 hours at room temperature to form the colloidal layer. Furthermore, to ensure complete soaking of the gelling material by the second mixture, an auxiliary shaker can be used to agitate the soaking. After soaking, the gelling material is removed, and it is measured that the gelling material has absorbed approximately 10-80% of its weight in the second mixture, i.e., the ratio of the gelling material to the second mixture absorbed into the gelling material is approximately 1:0.1-0.8 (weight ratio). According to a specific embodiment of the present invention, the gelling material absorbs approximately 80% of the weight of the second mixture, that is, the ratio of the gelling material to the second mixture absorbed into the gelling material is approximately 1:0.8 (by weight).

[0102] According to alternative embodiments of the present invention, the colloidal layer in the patch of the present invention is a non-homogeneous colloidal layer, wherein the following steps are included before performing the above-described step (4) of preparing the colloidal layer:

[0103] (3-2) The third mixture from step (3) is applied onto a silicone-containing hydrogel, wherein the silicone-containing hydrogel is a prepolymer formed by polymerizing a silicone-containing ethylene monomer.

[0104] According to an embodiment of the present invention, the third mixture from step (3) is applied to a silicone-containing hydrogel at a ratio of approximately 1:5-20 (by weight), for example, at a ratio of approximately 1:5, 1:5.5, 1:6, 1:6.5, 1:7, 1:7.5, 1:8, 1:8.5, 1:9, 1:9.5, 1:10, 1:10.5, 1:11, 1:11.5, 1:12, 1:12.5, 1:13, 1:13.5, 1:14, 1:14.5, 1:15, 1:15.5, 1:16, 1:16.5, 1:17, 1:17.5, 1:18, 1:18.5, 1:19, 1:19.5, or 1:20 (by weight). According to a specific embodiment of the present invention, the third mixture from step (3) is applied to a silicone-containing hydrogel at a ratio of approximately 1:9 (by weight). The silicone-containing hydrogel in this step is as described above and will not be repeated for brevity. The aforementioned "prepolymer" refers to a starting polymer that can be cured by photochemical, thermal, or chemical methods to obtain a crosslinked and / or polymerized polymer, wherein the crosslinked and / or polymerized polymer has a molecular weight much higher than that of the starting polymer. According to the present invention, the prepolymer is soluble in a solvent and can be used to produce a silicone-containing hydrogel colloid with a specific shape by casting in a mold.

[0105] According to certain embodiments of the present invention, the colloidal layer is cured by heating, and the gelling material is a thermosetting gelling material composed of at least one material selected from the group consisting of water, 1,3-butanediol, carboxymethyl cellulose, polyvinyl chloride, diethylene glycol, ethylene glycol, glycerol, hydroxyethyl cellulose, malic acid, poloxamer, polyethylene glycol, polypropylene glycol, polyvinyl alcohol, polyvinylpyrrolidone, and sorbitol. In one specific embodiment, the thermosetting adhesive material of the patch of the present invention is used in a specific operational embodiment. The thermosetting adhesive material of the patch of the present invention uses water, glycerin, malic acid, polyvinyl alcohol, polyvinyl carboxylate, carboxymethyl cellulose and hydroxyethyl cellulose, etc., and the composition ratio of each component is: 63.5% (by weight) water, 15% (by weight) glycerin, 8.5% (by weight) malic acid, 7% (by weight) polyvinyl alcohol, 3.2% (by weight) polyvinyl carboxylate, 1.4% (by weight) carboxymethyl cellulose and 1.4% (by weight) hydroxyethyl cellulose.

[0106] Various properties of the patch of the present invention can be tested using methods well-known in the art. For example, to analyze the cannabidiol release of the patch of the present invention, an in vitro artificial skin-penetrating model or an in vivo mouse animal experiment can be used, and / or combined with high performance liquid chromatography. In addition, to analyze the stability of the patch of the present invention, it can be tested using a cruelty test (i.e., accelerated test) well-known in the art; the cruelty test involves placing the patch of the present invention in a specific temperature environment higher than the normal storage temperature to test the stability of the patch. Depending on the experimental design, the test temperature of the cruelty test is based on the normal storage temperature, and then the test temperature is increased at intervals of 5°C or 10°C.

[0107] The following embodiments are provided to illustrate certain aspects of the invention, in order to facilitate implementation of the invention by those skilled in the art. These embodiments should not be construed as limiting the scope of the invention. It is believed that those skilled in the art, upon reading the description herein, can fully utilize and implement the invention without excessive interpretation. All publicly available documents cited herein are incorporated herein by reference in their entirety.

[0108] Example

[0109] Example 1 confirms the purity of cannabidiol.

[0110] First, the obtained cannabidiol raw material was detected by nuclear magnetic resonance (NMR) spectroscopy (400 millihertz (mHz)) and compared with the characteristic peaks of cannabidiol in existing published literature to confirm that the obtained cannabidiol raw material was indeed cannabidiol (data not shown).

[0111] Next, the obtained cannabidiol raw material was analyzed using high-performance liquid chromatography (HPLC) under the conditions set in Table 1 below. The experimental results are as follows: Figure 1 As shown in the small figures A and B, where Figure 1 Small figure A shows the cannabidiol raw material (experimental sample) intended for use in the preparation of the patch, while Figure 1 In Figure B, the sample is commercially available cannabidiol (reference standard). The experimental results show that at a concentration of 100 parts per million, the chromatographic characteristic peaks of the experimental sample's cannabidiol raw material are similar to those of the reference standard, and there are no other obvious noise characteristic peaks, indicating that the experimental sample is indeed high-purity (>95%) cannabidiol.

[0112] Table 1. Analytical setup conditions for high performance liquid chromatography (HPLC)

[0113]

[0114]

[0115] Example 2: Preparation of a multi-shell lipid nanoparticle composition containing cannabidiol

[0116] 2-1 Formulation of a multi-shell lipid nanoparticle composition containing cannabidiol

[0117] The cannabidiol-containing multi-shell lipid nanoparticle composition of the present invention was formulated using the formulations listed in Table 2 and the following steps.

[0118] Table 2. Formulation and particle size test results of the cannabidiol-containing multi-shell lipid nanoparticle composition.

[0119]

[0120]

[0121] First, the core material described in Table 2 is heated to approximately 90°C to a molten state. While the core material is in a molten state, the active ingredients (i.e., cannabidiol) listed in Table 2 are added to the core material at a ratio of approximately 1:1.6-16 (by weight), and the mixture is continuously heated and stirred to ensure that the active ingredients are evenly dispersed and dissolved in the core material.

[0122] (1) Experimental Example 1: The ratio of cannabidiol to core materials was approximately 1:13.3;

[0123] (2) Experimental Example 2: The ratio of cannabidiol to core materials was approximately 1:13.3;

[0124] (3) Experimental Example 3: The ratio of cannabidiol to core materials was approximately 1:13.3;

[0125] (4) Experimental Example 4: The ratio of cannabidiol to core materials was approximately 1:13.3;

[0126] (5) Comparative Example 1: The ratio of cannabidiol to core materials is approximately 1:4;

[0127] (6) Comparative Example 2: The ratio of cannabidiol to core materials is approximately 1:1.6;

[0128] (7) Comparative Example 3: The ratio of cannabidiol to core material is approximately 1:16;

[0129] (8) Comparative Example 4: The ratio of cannabidiol to core materials is approximately 1:4;

[0130] (9) Comparative Example 5: The ratio of cannabidiol to core material is approximately 1:1.6.

[0131] Next, the solubilizing and stabilizing material described in Table 2 is heated to approximately 90°C, and the mixture containing the active ingredient and the core material (hereinafter referred to as the first mixture) is added to the solubilizing and stabilizing material at a ratio of approximately 1:6.7-10.8 (by weight), and heating is continued to maintain the temperature at 90°C; wherein

[0132] (1) Experimental Example 1: The ratio of the first mixture to the solubilizing and stabilizing material was approximately 1:10.6;

[0133] (2) Experimental Example 2: The ratio of the first mixture to the solubilizing and stabilizing material was approximately 1:10.6;

[0134] (3) Experimental Example 3: The ratio of the first mixture to the solubilizing and stabilizing material was approximately 1:10.6;

[0135] (4) Experimental Example 4: The ratio of the first mixture to the solubilizing and stabilizing material was approximately 1:10.6;

[0136] (5) Comparative Example 1: The ratio of the first mixture to the solubilizing and stabilizing material is approximately 1:9.0;

[0137] (6) Comparative Example 2: The ratio of the first mixture to the solubilizing and stabilizing material is approximately 1:6.7;

[0138] (7) Comparative Example 3: The ratio of the first mixture to the solubilizing and stabilizing material is approximately 1:10.8;

[0139] (8) Comparative Example 4: The ratio of the first mixture to the solubilizing and stabilizing material is approximately 1:9.0;

[0140] (9) Comparative Example 5: The ratio of the first mixture to the solubilizing and stabilizing material is approximately 1:6.7.

[0141] Subsequently, the mixture containing the first mixture and the solubilizing stabilizer (hereinafter referred to as the second mixture) was emulsified and homogenized at a temperature of 80-95°C using a high-shear emulsifier at approximately 7500 rpm or a high-pressure homogenizer at approximately 600 bar. The second mixture was then rapidly cooled to room temperature for later use. The component ratios of the resulting cannabidiol-containing multi-shell lipid nanoparticle composition are listed in Table 2.

[0142] Particle size analysis was performed on all the above formulations, and the results are shown in Table 2 above. For different batches of the formulation in Experimental Example 2, particle size analysis was also performed, and the results are shown below. Figure 2 As shown, the average particle size is approximately 207.2 nm (between 205.1 and 544.8 nm), and the polydispersity index is approximately 0.392 (between 0.364 and 0.525).

[0143] 2-3 Stability testing of the multi-shell lipid nanoparticle composition containing cannabidiol

[0144] Stability tests were conducted on the multi-shell lipid nanoparticle composition containing cannabidiol (prepared from the experimental and control examples in Table 2). After measuring the particle size by taking about 2 ml, about 300 ml of the contents were returned to the bottle without being dispensed and left to stand at room temperature of about 28°C and refrigerated at about 4°C for 24 hours. The condition inside the bottle was then observed directly with the naked eye.

[0145] Visual observations showed that, compared to the microparticle compositions without added solid lipids (Experimental Example 1 and Control Examples 3-5), the microparticle compositions with added solid lipids (Experimental Examples 2-4 and Control Examples 1-2) exhibited significantly increased stability. This was because stability tests revealed that the microparticle compositions without added solid lipids separated into oil and water within approximately one day after the stability test. The cannabidiol multi-shell lipid nanoparticle composition of this invention represents an invention with unexpectedly advantageous stability.

[0146] 2-4 Testing the drug release rate of the cannabidiol-containing multi-shell lipid nanoparticle composition

[0147] To understand the effect of different proportions of solid and liquid lipids in the core material on the drug release of the active ingredient (cannabidiol), the following experiment was conducted.

[0148] The following steps were performed for this experiment. First, the three formulations from Experiments 2-4 in Table 2 were diluted 20 times with an organic solvent-free eluent (phosphate-buffered saline, PBS containing 6% polysorbate 80 or Tween 80). Next, the mixture was ultrasonically shaken for 10 minutes at room temperature to elute cannabidiol, followed by centrifugation at 15,000 rpm for 5 minutes. Afterward, the supernatant was diluted 10 times with the eluent, and the cannabidiol concentration in the eluent was analyzed using a UV-Vis spectrophotometer (UV-Vis measurement; absorption wavelength 280 nm).

[0149] The measured cannabidiol release rates are shown in Table 3 below. The experimental results show that the drug release rate of the formulation in Experimental Example 2 is 1.44 times higher than that of Experimental Example 4, and 1.31 times higher than that of Experimental Example 3. These results indicate that, in the cannabidiol-containing multi-shell lipid nanoparticle composition of the present invention, the ratio of solid lipids to liquid lipids in the core material has a significant impact on the drug release rate. Compared to formulations composed entirely of solid lipids (Experimental Example 4) and formulations with a higher proportion of solid lipids than liquid lipids (Experimental Example 3), an increased proportion of liquid lipids (Experimental Example 2) is beneficial for promoting the release rate of cannabidiol within an acceptable transdermal particle size range (50-500 nm), thereby enhancing the body's absorption of the drug and improving its bioavailability.

[0150] Table 3. UV-Vis measurement of cannabidiol release concentration in the eluent.

[0151]

[0152]

[0153] Example 3: Preparation of a colloidal layer of a multi-shell lipid nanoparticle composition containing cannabidiol

[0154] In this embodiment, the cannabidiol-containing multi-shell lipid nanoparticle composition obtained in Example 2 is further formulated into a homogeneous (as in Examples 3-1, 3-2, 3-3) or non-homogeneous (as in Examples 3-4) colloidal layer for further use in the patch of the present invention.

[0155] 3-1 Using UV-curable gelling materials

[0156] The second mixture prepared in Experimental Example 2 of Table 2 was added to the UV-curable gelling material listed in Table 4 below at a ratio of approximately 1:1.5 (by weight), and mixed evenly to obtain a third mixture. The third mixture was then irradiated with 400 watts of UV light for 30 seconds to form a gel, thereby obtaining the colloidal layer. The measured UV light intensity was approximately 1.68 joules / cm² / 30 seconds, and the concentration of the monomer 2-acrylamido-2-methylpropanesulfonic acid was found to be less than 800 parts per million.

[0157] Table 4 Formulations of UV-curable gelling materials

[0158] water 42.5% 2-Acrylamido-2-methylpropanesulfonic acid 42.5% Hydroxyethyl methacrylate 3.0% N,N'-Methylenebisacrylamide 0.9% 2-Hydroxy-2-methylphenylacetone 0.9% glycerin 10.2%

[0159] 3-2 Use thermosetting adhesives

[0160] The second mixture prepared in Experimental Example 2 of Table 2 was added to the thermosetting gelling material listed in Table 5 below at a ratio of about 1:1.5 (by weight), and mixed evenly to obtain a third mixture. The third mixture was then heated to about 90°C and gelled for 20 minutes to obtain the colloidal layer.

[0161] Table 5 Formulations of thermosetting adhesives

[0162]

[0163]

[0164] 3-3 Using silicone-containing hydrogel adhesives as forming materials

[0165] Five milliliters (approximately 5 grams) of the second mixture prepared in Experimental Example 2 of Table 2 were used to soak the silicone-containing hydrogel material (i.e., the silicone-containing hydrogel material was approximately 25 milligrams) in a ratio of approximately 1:0.005 (by weight) to obtain the colloidal layer. The silicone-containing hydrogel material was cured, and the soaking conditions were: 18 hours of standing soaking at room temperature followed by 6 hours of shaking soaking. The silicone-containing hydrogel material was composed of polydimethylsiloxane (PDMS), 2-hydroxy-2-methylphenylacetone (HMPP), and trimethylolpropane trimethacrylate (TMPTMA) in a ratio of approximately 1:0.14:0.01 (by weight).

[0166] Next, the prepared colloidal layer was extracted and analyzed using the following steps, and the experiment was repeated three times. First, the colloidal layer was washed with deionized water, then immersed in 1 mL of deionized water and ultrasonically agitated for 3 minutes, and the supernatant was retained to obtain the soaking solutions A to C. The colloidal layer was then further extracted with 1 mL of methanol and ultrasonically agitated for 3 minutes, followed by centrifugation at 10,000 rpm for 3 minutes, and the supernatant was collected to obtain the methanol extracts CL-A to CL-C. The obtained methanol extracts, together with the above-mentioned water soaking solutions, were analyzed for cannabidiol concentration using a UV-Vis spectrophotometer (UV-Vis measurement; absorption wavelength 220 nm) and particle size analysis (DLS) was performed to measure the particle size of the multi-shell lipid nanoparticles. The experimental results are shown in Table 6.

[0167] Table 6. Analytical results of UV-Vis measurement and particle size analysis.

[0168]

[0169]

[0170] Based on the experimental results in the table above, it is confirmed that the colloidal layer of this embodiment does indeed absorb cannabidiol and carrier (i.e., the second mixture) into the gelling material containing silicone hydrogel, and the gelling material absorbs approximately 20 mg of cannabidiol and carrier.

[0171] 3-4 Preparation of composite colloids

[0172] casting method

[0173] The third mixture prepared in Example 3-1 (before UV curing) was first poured into a portion (about 10% by weight) of the mold by injection molding and pre-crosslinked by UV irradiation. Then, the entire mold was filled with silicone water-based adhesive (about 90% by weight) and cured by UV irradiation again to form a composite colloid.

[0174] Dispensing method

[0175] The third mixture prepared in Example 3-1 (before UV curing) was dropped onto the surface of the silicone-containing water-based adhesive in a dropwise manner (the ratio of the third mixture to the silicone-containing water-based adhesive was approximately 1:9 (by weight)). After UV curing, a composite colloid was formed.

[0176] In summary, the patch containing cannabidiol multi-shell lipid nanoparticles prepared by this invention, after particle size analysis, has an effective average particle size of less than approximately 1500 nm. In some embodiments, the effective average particle size is approximately 100-600 nm, and in preferred cases, it is 100-300 nm. Furthermore, it exhibits high uniformity and good stability. Firstly, it improves the bioavailability of cannabidiol, enabling fluid-based administration. Secondly, it enhances the solubility of cannabidiol through the high specific surface area of ​​the nanocarrier, thereby increasing the solubility of poorly soluble molecules. Thirdly, it reduces the frequency of drug use by significantly extending the half-life of the active ingredient through the nanocarrier. Therefore, this invention effectively achieves its main objective: to provide a nanoparticle composition containing cannabidiol multi-shell lipid nanoparticles with uniform particle size distribution and high bioavailability. This invention also provides various formulation methods to facilitate the preparation of this composition into a patch capable of penetrating physiological barriers.

[0177] It is understood that the above description of the embodiments is merely illustrative, and those skilled in the art can make various modifications and alterations thereto. The above specification, examples, and experimental data provide a complete description of the structure and usage of the present invention as illustrative embodiments. Although the various embodiments of the present invention described above have certain characteristics, or refer to one or more individual embodiments, those skilled in the art can still make numerous modifications to the disclosed embodiments without departing from the spirit and scope of the present invention.

Claims

1. A patch containing cannabidiol, comprising a support and an adhesive layer adhered to said support, wherein... The colloidal layer comprises cannabidiol, a core material, a solubilizing and stabilizing material, and a gelling material, wherein the cannabidiol, the core material, and the solubilizing and stabilizing material together form a multi-shell lipid nanoparticle. The core material comprises lipids, and the lipids are composed of a solid lipid and a liquid lipid, wherein the weight ratio of the solid lipid to the liquid lipid is 1:0.25-1.5, and the solid lipid is disorbate diglyceride; the liquid lipid is triglyceride. The solubilizing and stabilizing material comprises water and a first surfactant; and the first surfactant is selected from the group consisting of cholesterol, lecithin, poloxamer, polyglycerol-10 oleate, polyethylene glycol-40 hydrogenated castor oil, polysorbate 80, and combinations thereof; and The content of cannabidiol accounts for 0.2-2% of the total mass of the colloidal layer.

2. The patch according to claim 1, wherein the weight ratio of cannabidiol: the core material: the solubilizing and stabilizing material: the gelling material is 1:1.6-16:17.4-183:30-300.

3. The patch as claimed in claim 1, wherein in the core material, the weight ratio of the solid lipid to the liquid lipid is 1:1.

5.

4. The patch of claim 1, wherein the core material further comprises a first antioxidant, a second surfactant, or a combination thereof; and the solubilizing and stabilizing material further comprises an alcohol, a second antioxidant, or a combination thereof.

5. The patch as described in claim 4, wherein... The alcohols are selected from the group consisting of ethanol, 2-(2-ethoxyethoxy)ethanol, polyethylene glycol 200-600, propylene glycol, glycerol, and combinations thereof; The first or second antioxidant is selected from the group consisting of toxoxelam, α-tocopherol, tocopheryl acetate, and combinations thereof; and The first surfactant or the second surfactant is selected from the group consisting of cholesterol, lecithin, poloxamer, polyglycerol-10 oleate, polyethylene glycol-40 hydrogenated castor oil, polysorbate 80, and combinations thereof.

6. The patch of claim 5, wherein the core material is composed of the lipids, the first antioxidant, and the second surfactant, and the lipids are composed of solid lipid disorbate and liquid lipid triglyceride, the first antioxidant is tococelen, and the second surfactant is poloxamer; and the solubilizing and stabilizing material is composed of water and the first surfactant, and the first surfactant is polysorbate 80.

7. The patch of claim 1, wherein the adhesive layer is formed via the following steps: (1) The cannabidiol and the core material are mixed in a weight ratio of 1:1.6-16 to form a first mixture; (2) The first mixture from step (1) is mixed with the solubilizing and stabilizing material at a weight ratio of 1:6.7-10.8 to form a second mixture; (3) The second mixture from step (2) is mixed with the gelling material at a weight ratio of 1:1.5 to form a third mixture; (4) The third mixture from step (3) is cured to form the colloidal layer; In the core material, the solid lipids and the liquid lipids are mixed in a weight ratio of 1:0.25-1.

5.

8. The patch of claim 7, wherein in the core material, the solid lipids and the liquid lipids are mixed in a weight ratio of 1:1.

5.

9. The patch of claim 7, wherein in step (4), the adhesive layer is cured by irradiation with ultraviolet light, and the adhesive material comprises a hydrophilic monomer, a crosslinking agent, and a photoinitiator, wherein The hydrophilic monomer is allyl methacrylate, 2-acrylamido-2-methylpropanesulfonic acid, cellulose acetate butyrate, cyclohexyl methacrylate, diacetone acrylamide, fluorosiloxane methacrylate, N-formylmethacrylamide, glyceryl methacrylate, hydroxyethyl methacrylate, isobutyl methacrylate, methacrylate, N,N-dimethylacrylamide, N-vinylpyrrolidone, polyethylene glycol diacrylate, poly(methyl methacrylate), poly(N-vinylpyrrolidone), siloxane methacrylate, triethylene glycol dimethacrylate, or a combination thereof. The crosslinking agent is tetraethylene glycol diacrylate, triethylene glycol diacrylate, ethylene glycol diacrylate, diethylene glycol diacrylate, tetraethylene glycol dimethacrylate, triethylene glycol dimethacrylate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, trimethylpropane trimethacrylate, isopentetrol tetramethacrylate, bisphenol A dimethacrylate, vinyl methacrylate, ethylenediamine dimethacrylamide, ethylenediamine diacrylamide, glycerol dimethacrylate, triallyl isocyanurate, triallyl cyanurate, allyl methacrylate, 1,3-bis(methacrylamidopropyl)-1,1,3,3-tetra(trimethylsiloxy)disiloxane, N,N'-methylenedimethacrylate, etc. Methacrylamide, N,N'-methylenebisacrylamide, N,N'-vinylbisacrylamide, N,N'-vinylbisacrylamide, 1,3-bis(N-methacrylamidopropyl)-1,1,3,3-tetra(trimethylsilyloxy)disiloxane, 1,3-bis(methacrylamidopropyl)-1,1,3,3-tetra(trimethylsilyloxy)disiloxane, 1,3-bis(acrylamidopropyl)-1,1,3,3-tetra(trimethylsilyloxy)disiloxane, 1,3-bis(methacryloyloxyethylureapropyl)-1,1,3,3-tetra(trimethylsilyloxy)disiloxane, trimethylolpropane trimethacrylate or combinations thereof; and The photoinitiator is benzoin methyl ether, diethoxyacetophenone, 2,4,6-trimethylbenzoyl diphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-4-N-propylphenylphosphine oxide, bis-(2,6-dichlorobenzoyl)-4-N-butylphenylphosphine oxide, 1-hydroxycyclohexylphenyl ketone, or 2-hydroxy-2-methylphenylacetone.

10. The patch of claim 9, wherein in the adhesive material, the monomer is composed of 2-acrylamido-2-methylpropanesulfonic acid (AMPS) and hydroxyethyl methacrylate (HEMA), the crosslinking agent is N,N'-methylenebisacrylamide (NMBA), the photoinitiator is 2-hydroxy-2-methylphenylacetone (HMPP), and the weight ratio of AMPS:HEMA:NMBA:HMPP is 1:0.01-1:0.01-0.5:0.01-0.

5.

11. The patch of claim 10, wherein the weight ratio of AMPS:HEMA:NMBA:HMPP is 1:0.07:0.02:0.

02.

12. The patch as claimed in claim 9, wherein in step (4), the third mixture from step (3) is irradiated with 400 watts of ultraviolet light for 5 to 60 seconds.

13. The patch of claim 7, wherein steps (3) and (4) are replaced by the following steps: (3-1) The second mixture from step (2) is used to soak the gelling material at a weight ratio of 1:0.003-0.007 to form the colloidal layer; wherein the gelling material absorbs 10-80% of the weight of the second mixture, and the gelling material is a silicone-containing hydrogel, which is polymerized from a silicone-containing ethylene monomer. The silane-containing vinyl monomer is polydimethylsiloxane, N-[tris(trimethylsiloxy)silylpropyl]acrylamide, N-[tris(trimethylsiloxy)silylpropyl]methacrylamide, tris(trimethylsiloxy)silylpropyl methacrylate, methacryloyloxyalkylsiloxane, 3-methacryloyloxypropylpentamethyldisiloxane, bis(methacryloyloxypropyl)tetramethyl-disiloxane, monomethacrylated polydimethylsiloxane, monoacrylated polydimethylsiloxane, mercapto-terminated polydimethylsiloxane, or a combination thereof.

14. The patch of claim 7, wherein in step (4), the adhesive layer is cured by heating, and the adhesive material is composed of water, glycerin, malic acid, polyvinyl alcohol, polyvinyl carboxylate, carboxymethyl cellulose, and hydroxyethyl cellulose.

15. The patch of claim 1, wherein the effective average particle size of the multi-shell lipid nanoparticles is 100-1500 nanometers.

16. The patch of claim 15, wherein the effective average particle size of the multi-shell lipid nanoparticles is 100-600 nanometers.

17. The patch of claim 16, wherein the effective average particle size of the multi-shell lipid nanoparticles is 100-300 nanometers.

Citation Information

Patent Citations

  • Use of cannabidiol prodrugs in topical and transdermal administration with microneedles

    US20110052694A1

  • Transdermal delivery of cannabidiol

    US20210259989A1